Eksistensi Advokat Bagi Korban Dalam Peradilan Militer - Rengrengulu, David Masaluri; Titahelu, Juanrico Alfaromona Sumarezs; Supusepa, Reimon (PATTIMURA Law Study Review, 2025)
The existence of victim advocates in military justice has an important role to ensure the protection of the rights of victims involved in military cases. Military justice generally focuses more on handling violations of military discipline and criminal offenses committed by members of the military, which often pays less attention to the rights of victims. Therefore, the presence of advocates for victims is needed to provide legal assistance and ensure victims' rights are fulfilled, such as the right to information, protection, and a fair trial. This study aims to analyze the role of advocates in assisting victims in military courts, identify obstacles faced, and provide recommendations to improve victims' access to justice in the military justice system. Using a qualitative method through case studies and analysis of relevant legislation, this research found that the presence of advocates for victims not only supports the principles of justice and legal protection, but also encourages reforms in the military justice process to be more pro-victim. The results of this research are expected to be the basis for strengthening regulations related to the role of advocates in military justice, in order to realize a justice system that is inclusive and responsive to victims' rights.